Answer:
3
Step-by-step explanation:
Answer:
24.5
Step-by-step explanation:
Answer:
K'= (-1,-1)
J'= (-1,-5)
L'= (0,-3)
Step-by-step explanation:
What you do here is, input the (x,y) coordinates into the translation.
For example, the original point K is (-3,5). Insert this into the translation.
(-3,5) → (-3+2, 5-8) = (-1,-3)
Repeat this for the next coordinates of L and J.
J= (-3,3)
(-3,3) → (-3+2, 3-8) = (-1,-5)
L= (-2, 5)
(-2, 5) → (-2+2, 5-8) = (0,-3)
<span> f(x)=4x^8+7x^7+1x^6+
</span>∴<span> f(-2)=4(-2)^8+7(-2)^7+1(-2)^6+1
</span>∴ <span>f(-2)=(4x256) + (7x-128) + (1x64) +1
</span>∴ <span>f(-2)=1024 - 896 + 64 +1
</span>∴ <span>f(-2)= 193</span>
Sonia practices for 96 mins (1 hour 36mins ) 0.8 = 80%